Erosion Surfaces of the Land Between Iznik-Mekece (Turkey) - YAZICI, Oznur (International Journal of Geography and Geology, 2018)
The study area begins from the eastern part of the Lake Iznik which is in the southeast of Marmara Region in Northwest Turkey, and extends to Mekece. The area is part of the North Anatolian Fault Line, which has been operating since Miocene. Gemlik Gulf-Iznik Depression-Karadin Trough, and Pamuk Plain are the depression series from west to the east which developed due to the fault. During the cool and rainy periods of the Pleistocene, a part of the depression filled with water and became the Lake Iznik. In this period, there have been level changes on the lake due to the climate oscillations and some lacustrine terraces formed. Main geomorphological units in the study area are; high mountain ranges, high and low plateaus, plains and flat fields. Erosion surfaces, which spread widely in the study area, have been handled and evaluated according to Prof. Dr. Oğuz Erol’s method. Erosion surfaces were dated as Lower-Middle Miocene surfaces, Upper Miocene surfaces and Pliocene surfaces by applying Erol’s ‘Relation Method Between Slopes and Contour Lines’. Some of these surfaces are valuable for the settlement and agriculture because of the small amount of the slopes. It can be said that the research area has a polycyclic feature, and it is in the late youth stage of geomorphologic development.